Assessment of Knowledge, Attitude and Practice towards Sustainability Aspects among Higher Education Students in Qatar - Shaikha R. Al-Nuaimi (19488232) (2022)
Sustainable development necessitates that societies design activities to meet human needs while protecting the planet’s life-support systems in consideration of depleting natural resources and concern for the state of the resources and climate. Sustainable development emphasizes the conservation and enhancement of natural resources by modifying how they are utilized, highlighting the role of nations in meeting their basic needs for employment, food, energy, and water. Higher education institutions (HEI), such as universities, should be able to produce a workforce that satisfies the demand for competent stakeholders and contributes to the successful implementation of the United Nations Sustainable Development Goals (SDGs) by integrating Education for Sustainable Development (ESD) and sustainability principles into their institutional strategy and organizational culture. This research evaluates the sustainability consciousness of higher education students and the effect of ESD on higher education students in Qatar. The study employs the sustainability consciousness questionnaire (SCQ) to assess HEI students’ sustainable development knowledge, attitudes, and behaviors while considering educational system characteristics such as curriculum, community, and the campus. The questionnaire was distributed among students from different fields and universities in Qatar. Results were analyzed using statistical tools to show that over 80% grasp sustainability-related knowledge. This value gradually decreases in attitudes and behaviors based on evaluating the pro-sustainability student responses. Further, over 60% of the surveyed students indicate external factors excluding the educational system characteristics to have the most profound effect on providing and developing the student’s knowledge, attitudes, and behaviors towards sustainable development. Understanding the current state of sustainability education in HEI can lead to an improved preparation of the global youth with the necessary skills to meet the sustainability challenges and to be involved in establishing and sustaining long-term progress that can aid in achieving SDG goals and drive sustainability action. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su142013149